Strengthening student tolerance through the integration of Moi community customary values in citizenship learning - Ihsan; Sapriya; Elly Malihah; Dadang Sundawa; Raisa Anakotta (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
This study highlights the significance of integrating Moi community customary values into civic education to encourage students to develop a more tolerant mindset. This study uses a qualitative methodology to incorporate values such as solidarity, mutual respect, and togetherness into the learning process. According to the study's findings, including these values in the education of students not only enhances their capacity to exhibit tolerance towards others but also contributes to a greater sense of solidarity with other individuals and an increased sense of national pride. Furthermore, the incorporation of Moi traditions helps create an inclusive learning environment that equips students with the practical skills necessary to manage diversity. This study found that to successfully implement culture-based education to create a harmonious and pluralistic society, it is required to secure broader support from stakeholders, including educators, policymakers, and local communities.